ANALISIS DAN PERBAIKAN STRUKTUR SKALA UPAH PADA CV LIGHTHOUSE INFORMATIKA SOLUSINDO MENGGUNAKAN METODE DUA TITIK - Rafly Adha Farisi; Faza Mazaya Athallahputwa; Nakami Fadhilah Hamida; Husna Yumna Aqila (Jurnal Pijar, 2026)
Employment conditions in Indonesia demand a transformation of human resource management into a structured system in accordance with Law No. 6 of 2023 and Government Regulation No. 36 of 2021. This study aims to formulate a strategic Wage Structure and Scale (SSU) framework at CV Lighthouse Informatika Solusindo, which currently operates informally and faces regulatory gaps. Using a quantitative descriptive approach, primary data were collected through questionnaires and interviews, followed by salary mapping analysis, minimum wage comparisons, and two-point method calculations. The results indicate that the actual compensation system lacks a formal structure, with operational positions such as Technicians and Administration still receiving wages below the 2026 NTB UMP of IDR 2,673,861, while the 2026 Mataram UMK standard of IDR 3,019,015 is only met by managerial levels. The two-point method calculation produced a 5-grade job structure where midpoint values reveal that actual salaries for Grades II to IV are significantly below the recommended standards, while Grade V (Director) is already at an ideal position. These findings imply the need for salary distribution adjustments to be more proportional to job responsibilities to create internal equity, increase employee motivation, and ensure the company's legal compliance